DUE DILIGENCE NOTARY PRACTICES BEFORE AND AFTER THE COMPANY'S CAPITAL MARKET LISTING AS A LEGAL ENTITY - Wijaya, Yasmin; Efendi, A; Noor, Azman Mohd. (SYNTIFIC, 2025)
Background. Businesses must finish the required paperwork and submit registration statements to the Capital Markets and Financial Institutions Supervisory Agency, which is assisted by organizations and experts, in order to participate in the capital market, which involves the public offering and selling of securities from publicly traded companies. The purpose of this research purpose was to determine the use of due diligence notaries before and following the company's legal entity listing in the stock market. Research Method. This research was qualitative, normative, and descriptive-analytical, which explains information and facts about the use of the openness principle and notary due diligence both before and after the Limited Liability Company's listing on the Capital Market. Findings. The implementation of notary due diligence requires the use of the capital market's openness concept. This implies that the notary confirms the company's information, which would be included in the deed he drafts, prior to performing his obligations in creating deeds. Making changes to the articles of organization, minutes of the general meeting of shareholders, deeds of agreement for public offers, and registration with the Capital Markets and Financial Institutions Supervisory Agency are among the notary's duties both prior to and following listing. Conclusion. Notaries must make sure that a deed has the right intent, content, and purpose while abiding by all applicable laws, statutes, rules, and the code of ethics.